Perceptions of Teacher and Students on the Use of E-Mail as A Medium in Distance Learning - Nashruddin Nashruddin; Fiptar Abdi Alam; Novalia Tanasy (Berumpun: International Journal of Social, Politics, and Humanities, 2020)
The covid-19 pandemic that hit the world including Indonesia has caused the teaching and learning system change from face-to-face in the classroom to distance learning or online learning. Online learning requires teachers and students to be able to use the information and communication technology (ICT). In ELT, the learning system is also implemented online. One of platforms commonly used in online communication is e-mail. This current study aims to describe: (1) teacher’s perceptions about the use of e-mail as a learning medium in ELT, (2) students’ perceptions about the use of e-mail as a learning medium in ELT. The subjects of this descriptive qualitative research were an EFL teacher and 20 students at a senior high school in Barru. For collecting data, the researchers applied questionnaire, documentation, and interview. Data was analyzed inductively or qualitatively. The results indicated the teacher’s perceptions on the use of e-mail in learning that email is an effective device, e-mail can be used to send many documents, e-mail as a tool to achieve learning objectives, and e-mail makes learning easier. Students’ perceptions on the use of e-mail are e-mail can be used for getting learning materials, e-mail is easy to use, and students can access various assignments on email. However, a small number of students still encountered obstacles in using email as a learning medium.